Laboratory Investigation on the Effectiveness of Stone Barrier in Channel Flow on Runoff and Soil Loss in Black Soils of Karnataka - A.K. Singh,; Mahesh Kothari,; P.K. Mishra,; R.C. Purohit, (Journal of Soil and Water Conservation, 2022)
A laboratory study was conducted using a tilting hydraulic flume to find the effect of varying discharge rates on runoff and soil loss channel flow for vertisols. The flume had perforated bed for collection of deep drainage and ‘V’ notch for runoff measurement. In the study, the flume was kept at 1% slope for three varied inflows 5.0, 7.5 and 10.0 Ips for 15 minutes duration. Results of the study showed that percentage of runoff in the bare soil condition was 66.90, 68.60 and 70.18 per cent while under the stone barrier condition it was 61.00, 63.16 and 65.30 per cent, respectively, of the inflow rates of 5.0, 7.5 and 10.0 Ips. The stone barrier reduced runoff by 9, 8 and 7 per cent. Reduction in soil loss due to stone barrier was 62, 57 and 56 per cent under three different inflow rates, respectively, in comparison to bare soil condition. The results may be useful for planning and design of stone barrier in field channels and waterways in black soils of semi arid region in Karnataka.